THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION AND SELF-EFFICIENCY ON ENTREPRENEURSHIP INTENTION (STUDY OF CLASS XII STUDENTS DEPARTMENT OF MARKETING AND ACCOUNTING AT ISLAM BATU VOCATIONAL SCHOOL) - Martyajuarlinda, Atricia (Nusantara Economics and Entrepreneurships Journals, 2023)
This study aims to know the influence of entrepreneurship education and self-efficacy toward student's intention of entrepreneurship. This research is a class XII student of marketing and accounting at SMK Islam Batu and the sampling of this research is simple random sampling. Based on the result, entrepreneurship education and self efficacy show a significant influence on student’s intention of entrepreneurial at SMK Islam Batu